KEAWETAN ALAMI TRUBUSAN JATI (Tectona grandis Linn f.) UNGGUL NUSANTARA TERHADAP RAYAP KAYU KERING (Cryptotermes cynocephalus Light) - meiganati, kustin bintani (Fakultas Kehutanan Universitas Winaya Mukti, 2024)
Jati Unggul Nusantara (Tectona grandis Linn f.) or commonly known as JUN is an engineered product to reduce the teak cycle. Teak is one type of tree whose wood is in great demand because it is known to be the strongest and has a high selling value. Durability is the natural resistance of wood to wood-destroying organisms. The main cause of the low durability of a wood is due to termite attack. Termite attacks can have an impact on the selling value of a wood, therefore research on the natural durability of wood needs to be done. This study aims to determine the value of natural durability of JUN wood from dry wood termites. This research was conducted for 90 days of observation. The results showed that the natural durability of the JUNÂ shoots in the Experimental Garden of the UNB was classified as not resistant to dry wood termite attacks or was in durable class IV. This statement was obtained from the results of research on weight loss and low termite mortality. Judging from the low natural durability of the JUNÂ branches located at the Experimental Garden of the UNB, the wood must be preserved before being used to increase its service life. Preservation method that can be used is the hot-cold preservation method which can produce higher preservative retention.Key words : JUN, Dry Wood Termite, Natural Durability.